Explorations on the continuous oxidation kinetics of diesel PM from heavy-duty vehicles using a single ramp rate method. (15th July 2019) - Gao, Jianbing; Chen, Haibo; Chen, Junyan; Ma, Chaochen; Tian, Guohong; Li, Ying
Highlights: Negative apparent activation energy was observed during PM oxidation. Abnormal phenomenon disappeared after PM was devolatilized at high temperature. Hydrogen bonding complex formed in PM oxidation led to the abnormal phenomenon. Abstract: Particulate matter (PM) emitted by internal combustion engines has brought about serious environmental problems. Investigations of the PM oxidation behaviors and kinetics make the foundations of decreasing PM emission and working out the regeneration problems of PM capture devices. In this paper, the oxidation kinetics and microstructure evolutions of diesel PM in the oxidation process were researched. The results showed that thermogravimetric analysis (TGA) temperature history had a limited influence on the tendency of the oxidation kinetics. The volatilization of the organic compounds dominated the mass loss without any heat release at the initial stage of PM oxidation. The abnormal phenomenon (negative apparent activation energy) was observed in the oxidation process when the oxidation temperature was in the range of 200 °C–340 °C, which was ubiquitous during PM oxidation. However, the abnormal phenomenon disappeared if the PM sample was pre-treated to remove the volatile organic compounds (VOC), with the result that the phenomenon was caused by the VOC. The hydrogen bonding complex was formed in that temperature range, where the energy of the hydrogen bonding complex was lower than the value of the reactants, which caused the negative apparent activation energy. The apparent activation energy increased gradually when the temperature was higher than 340 °C.